2020
DOI: 10.3389/feart.2020.584001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the North Pacific Victoria Mode on the Madden–Julian Oscillation

Abstract: Using the observational data and the Coupled Model Intercomparison Project phase 5 (CMIP5) models this study examined the influence of the North Pacific Victoria mode (VM) on the Madden–Julian Oscillation (MJO). The results show that the February–April VM had a significant influence on the development and propagation of the MJO over the equatorial central-western Pacific (ECWP) during spring (March-May) between 1979 and 2017. Specifically, MJO development was favored more by positive VM events than negative VM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…In addition, the continental high can prevent cold air from the Arctic to intersect with warm air from the equator, resulting in a build‐up of warm air that can easily lead to heatwaves (Luo et al ., 2020). In general, the sea‐land‐atmosphere interaction has been considered as one of the most important factors affecting atmospheric circulations and climate events (Zhang et al ., 2011; Bollasina and Ming, 2013; Du et al ., 2019; Wen et al ., 2020; Yang et al ., 2020). Previous studies have found that warmer sea surface temperatures (SSTs) in the North Atlantic and North Pacific could enhance the temperature in North China (Zhang et al ., 2018a; Ding et al ., 2020; Zhang et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the continental high can prevent cold air from the Arctic to intersect with warm air from the equator, resulting in a build‐up of warm air that can easily lead to heatwaves (Luo et al ., 2020). In general, the sea‐land‐atmosphere interaction has been considered as one of the most important factors affecting atmospheric circulations and climate events (Zhang et al ., 2011; Bollasina and Ming, 2013; Du et al ., 2019; Wen et al ., 2020; Yang et al ., 2020). Previous studies have found that warmer sea surface temperatures (SSTs) in the North Atlantic and North Pacific could enhance the temperature in North China (Zhang et al ., 2018a; Ding et al ., 2020; Zhang et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The temporal variability of the VM index has a significant influence on the surrounding Pacific climate, including the Pacific Intertropical Convergence Zone (ITCZ) precipitation (Ding et al, 2015a), the anticyclone over the western North Pacific, and the winter rainfall over South China (Zou et al, 2020) and the western North Pacific tropical cyclone frequency (Pu et al, 2018). It can also be the linkage between North Pacific Gyre Oscillation and ENSO (Ding et al, 2015b) and contribute to the development and propagation of the Madden-Julian Oscillation (Wen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%